Immune-related intestinal pseudo-obstruction caused by immune checkpoint inhibitors: case report - Qian, Yimeng; Zhi, Zheng; Ai, Jing; Kang, Lin; Qiu, Gang; Huang, Xin; Zhao, Jing (Frontiers in Oncology, 2024)
Intestinal obstruction, a rare manifestation of immunotherapy-related gastrointestinal adverse events, can be severe and even life-threatening with intestinal perforation. We present a 64-year-old man with HCC and currently under the therapy with Pembrolizumab, who was admitted in our hospital with abdominal distension. Radiologic findings were consistent with small bowel ileus. After conservative treatment, the patient underwent colonoscopy where no cause of ileus was discovered. The patient received high-dose prednisone due to the side effects of immune checkpoint inhibitor therapy. This resulted in a gradual improvement of symptoms.